A Review of Functional Properties and Applications of Legume‐Based Edible Coatings - A. K. A. N. W. M. R. K. Thamarsha; Nishant Kumar; Pratibha; Kiran Mor; Ashutosh Upadhyay; Hemanth P. K. Sudhani; Venkata Sarath Pamu (Legume Science)
ABSTRACT Legumes are rich in starch, proteins, lipids, vitamins, and minerals, making them a better source for developing films with high nutritional value. They have become a sustainable and eco‐friendly coating to prolong the shelf life of perishable products while preserving both quality and safety. Legume‐based polysaccharides and proteins are cost‐effective materials to use as an alternative to synthetic materials. Additionally, legume‐based edible coatings are gluten free and acceptable to consumers with dietary restrictions for coatings derived from nonplant sources. Their use in edible coating further extends the economic significance of legumes. The physicochemical properties of these coatings may vary based on several factors including composition of the film, conditions of processing, and additives used. Legume‐based edible coatings and films hold the ability to enhance the shelf life and quality of food items by acting as barriers against oxygen, moisture, and solute transfer. Also, they can aid in maintaining the nutritional value, flavor, and sensory qualities of food products. Incorporation of bioactive compounds, such as antioxidants and antimicrobials, into legume‐based coatings further enhances their functionality in food preservation. This article provides an in‐depth review of the current state of research on legume‐based edible coatings, focusing on their development, physical and mechanical properties, applications in food preservation, and future scope.